The impact of cold chain temperature abuses on the quality of frozen strawberries (Fragaria ×ananassa) - Rui Cruz; Margarida Vieira; Cristina Silva (International Journal of Food Studies, 2013)
The quality of frozen foods can be negatively affected if improper storage and distribution temperatures are allowed. The objective of this study was to investigate the effect of freeze-thaw cycles, which may occur in the cold chain, on colour (Lab, Total Colour Differences (TCD), chroma and hue angle) and vitamin C (ascorbic and dehydroascorbic acids) content of frozen strawberries (Fragaria ×ananassa, Duschesne, cv. Selva). A plan of temperature abuses (TAs) was established, based on a real situation, and applied to frozen strawberries during a four month frozen storage period. The results showed that the lightness (L) was the only parameter that was not significantly affected by range of TAs studied. The colour showed some variation on the parameters a, b, TCD, chroma and hue angle. During TAs, ascorbic acid decreased about 75% and dehydroascorbic acid increased 73%. The non-abused strawberry samples showed better overall appearance than the abused samples. This work contributes to an understanding of the quality changes of frozen strawberries that might occur during frozen storage and cold chain distribution.